Liquidity in government versus covered bond markets - Jens Dick-Nielsen; Jacob Gyntelberg; Thomas Sangill (Danmarks Nationalbank, 2012)
We present findings on the secondary market liquidity of government and covered bonds in Denmark before, during and after the 2008 financial crisis. The analysis focuses on wholesale trading in the two markets and is based on a complete transaction level dataset covering November 2007 until end 2011. Overall, our findings suggest that Danish benchmark covered bonds by and large are as liquid as Danish government bonds - including in periods of market stress. Before the financial crisis of 2008, government bonds were slightly more liquid than covered bonds. During the crisis, trading continued in both markets but the government bond market experienced a brief but pronounced decline in market liquidity while liquidity in the covered bond market was more robust - partly reflective of a number of events as well as policy measures introduced in the autumn of 2008. After the crisis, liquidity in the government bond market quickly rebounded and government bonds again became slightly more liquid than covered bonds.
Keywords: E43; G12; G21; 330; bond market liquidity; government bonds; covered bonds; price impact; Öffentliche Anleihe; Rentenmarkt; Marktliquidität; Dänemark